Implementation of Google Calendar As an Android-based Agenda Application - ., Marsofiyati (KnE Social Sciences, 2019)
This study aims to describe optimizing the implementation of Google Calendar as an Android-based agenda application. The research method in this study is a survey method. State of the art in previous studies have discussed the importance of technology in managing the agenda of technology activities mobile based on operations Android or Information and Communication Technologies (ICT). (1) Lack of the contention that the multi-faceted challenges of service leadership about communication support, for example, communicate between secretary and leader to manage schedule (2) Many studies only designed and built an application that how to manage the Agenda but had not examined the optimization of these applications. (3) There are still many users, especially the leaders and secretaries who don’t know how to operate Google Calendar. Use of electronic calendars is very useful for someone who has a very tight meeting schedule. The Google Calendar application is currently used by almost all users of webmail and android, but it is still rare to do research on the application. Design a reminder application on mobile-based academic activities to distribute and remind lecturers and students in carrying out academic activities on schedule. The design application to simplify schedule management, create and present the agenda to the Chancellor is made with its own scheduling application, does not optimize Google Calendar as an existing application. Google Calendar is an application that can help a good schedule and remind schedules regularly so that users do not worry about skipping a schedule that has been set up even if the work piles up. Keywords: office administration application, secretary, scheduler, time schedule